Hybrid Organic/Inorganic Nanostructures for Highly Sensitive Photoelectrochemical Detection of Dissolved Oxygen in Aqueous Media. (16th June 2015) - Bellani, Sebastiano; Ghadirzadeh, Ali; Meda, Laura; Savoini, Alberto; Tacca, Alessandra; Marra, Gianluigi; Meira, Rui; Morgado, Jorge; Di Fonzo, Fabio; Antognazza, Maria Rosa
Abstract : Precise, reliable, and remote measurement of dissolved oxygen in aqueous media is of great importance for many industrial, environmental, and biological applications. In particular, photoelectrochemical sensors working in differential mode have recently demonstrated promising properties, in terms of stability, sensitivity, and application potential. Here, a new approach is presented, combining visible light sensitivity, efficient photocurrent generation, and solution‐processed fabrication methods of conjugated polymers, with charge carriers selectivity, energetic alignment favorable to efficient interfacial charge transfer and high surface area achievable by using metal oxide nanostructures. Extensive characterization and optimization of the hybrid organic/inorganic system are carried out, leading to the realization of an oxygen sensor device, based on nanostructured palladium oxide/poly[(9, 9‐dioctylfluorenyl‐2, 7‐diyl)‐ alt ‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole]/[6, 6]phenyl‐C61‐butyric acid methyl ester (PdO/APFO‐3:PCBM) as materials of choice. State‐of‐the‐art sensitivity, amounting at −5.87 μA cm −2 ppm −1, low background signal, in the order of −4.85 μA cm −2, good electrochemical stability for more than 2 h of continuous functioning and high reproducibility of the signal over the pH 1 to 10 range, are reported, making the hybrid device suitable for several practical uses. The results fully validate the mixed organic/inorganic approach for photoelectrochemical applications, and pave the way for its further exploitation in fields like waste water treatment, environmental monitoring, and water splitting. Abstract : A photoelectrochemical sensor for dissolved oxygen, based on the hybrid interface between an organic semiconductor and a nanostructured metal oxide, is realized. State‐of‐the‐art sensitivity, good electrochemical stability, and high reproducibility in different environmental conditions, ranging from acid to basic pH, are reported, making the polymer‐based device suitable for applications in waste water treatment, environmental monitoring and water splitting.